A pest of stuffed museum specimen Anthrenus scrophulariae (L.) (Coleoptera: Dermistidae) (University Journal of Zoology, Rajshahi University, 2008)
A pest of stuffed museum specimen, Anthrenus scrophulariae is known as carpet beetle. It is a serious and destructive coleopteran insect to stuffed and preserved museum bird and mammal specimens. The larvae devoured the feather, hair and skin of stuffed animals. The stuffed animals became feather or hairless and ultimately destroyed. Food and feeding habits and development of larvae were evaluated. The life history also observed in room temperature. Mean length of mature larvae was 3.16±072; 3.11±054; 2.75±077; 2.92±046 and 2.81±059 mm for feather, leather of goat and cow, dried cocoon of silkworm, dried insects and hair of mammal respectively. Number of eggs varied from 41-54 with a mean of 47.80 in the case of females which supplied food. No food supplied female laid 28-33 eggs. The mean length and breadth of eggs was 0.43±.112 and 0.212±0.54 respectively. Incubation period varied from 12-18 days. Larval period was varied from 140-148 days. Larvae passed 6 instar larvae is brownish in colour and very hairy. Pupal period varied 18-20 days. Mean length of pupae was 3.75±0.30 and breadth 1.87±0.05 mm. The duration to the life cycle (egg to the death of adult) of the carpet beetle, A. scrophulariae was ranged 182-199 days. Key words: museum specimen A. scrophulariae Univ. j. zool. Rajshahi Univ. Vol. 26, 2007. pp. 99-102